Excessive Eutrophication as a Chemical Barrier for Fish Fauna Dispersion: A Case Study in the Emblematic Tietê River (São Paulo, Brazil) - Urbanski, Bruna [UNESP]; Nogueira, Marcos [UNESP] (MDPI, 2024)
The Tietê River receives most of the effluents and diffuse wastes from the São Paulo metropolis (21.9 million inhabitants). The study aimed to assess the extent to which environmental changes affected the fish fauna. We compared, in rainy and dry seasons, three sites in Tietê and three in tributaries with much better water quality conditions. No physical barriers exist between the sites. Fish were sampled with gillnets (exposed overnight) and the assemblage’s ecological attributes calculated. Water depth, transparency, temperature, electrical conductivity, dissolved oxygen, turbidity, total dissolved solids, pH, redox potential, total phosphorus, total nitrogen, and chlorophyll were simultaneously determined. Low oxygen concentrations (near zero in the rainy period), and the opposite for nutrients and total solids, separated the predominantly hypereutrophic Tietê from the tributaries (PCA). Differences in the fish assemblages were also evidenced (nMDS), including a higher richness per sample in tributaries (11 to 14 spp.) compared to Tietê (3 to 4 spp.). Siluriformes with accessory breathing dominated in Tietê and the highly tolerant detritivorous Prochilodus lineatus (the main commercial fish) was the only species found in all sites. The species correlated positively with oxygen in the tributaries and with turbidity, redox potential, and nutrients in Tietê (DistLM) (rainy season). Recovery measures are urgently required.